Reliability, validity, and minimal clinically important differences for the Thai-version of the Aberdeen Varicose Vein Questionnaire (AVVQ-Thai) in patients with chronic venous disease [version 2; peer review: 1 approved, 2 approved with reservations] - Suchat Wongsuwanich; Chaowanun Pornwaragorn; Chumpon Wilasrusmee; Termpong Reanpang; Pinit Noorit; Boonying Siribumrungwong; Kittipan Rerkaserm; Andrew Malcolm Garratt; Thoetphum Benyakorn; Saritphat Orrapin; Kanoklada Srikuea (F1000Research)
Background Patient-reported outcome measures (PROMs) are essential for assessing the health of patients with chronic venous disease (CVD). Therefore, we aimed to translate the Aberdeen Varicose Vein Questionnaire into Thai language (AVVQ-Thai) and evaluate its reliability and validity. Minimal clinically important differences (MCID) of the AVVQ-Thai also be estimated. Methods International standards for PROM translation were followed including the forward-backwards translation of the AVVQ. Patients with Clinical-Etiology-Anatomy-Pathophysiology (CEAP) C2-C6 with truncal reflux were prospectively included. Venous interventions were used to treat reflux and varicosities. Patients’ characteristics, venous clinical severity scores (VCSS), EuroQol EQ-5D, and AVVQ-Thai were collected pre- and one-month post-intervention. AVVQ-Thai was also collected one to two weeks after the initial visit by reply-paid postal questionnaire. Results The study included 119 patients (30% C2, 29% C3, 28% C4, 11% C5, and 2% C6). The AVVQ-Thai had good internal consistency with Cronbach’s alpha of 0.783 and moderate reliability with the intraclass correlation coefficient of 0.67 (95%CI: 0.50, 0.79). The AVVQ-Thai was significantly correlated with VCSS and was able to discriminate patients with different levels of health problems as assessed by EQ-5D at both pre-and post-intervention, demonstrating good construct and discriminative validity. The median AVVQ scores improved significantly after intervention from 15.4 (IQR 8.3, 24.2) to 4.2 (IQR 1.3, 8.4) in C2-C3, and 18.9 (IQR 14.1, 25.5) to 7.3 (IQR 4.6, 16.3) in C4-C6. The MCID of the AVVQ was 6.21 on the 0-100 scale, which equates to the level of difference necessary to be clinically meaningful. Conclusions AVVQ-Thai has satisfactory evidence for internal consistency, reliability, validity, and responsiveness to change and is recommended for application in Thailand.